2003
DOI: 10.1105/tpc.009415
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Division in Fucoid Zygotes Is Positioned by Telophase Nuclei

Abstract: The relative contributions of cell polarity and nuclear position in specifying the plane of asymmetric division in fucoid zygotes were investigated. In zygotes developing normally, telophase nuclei were positioned parallel to the polar growth axis, and the division plane bisected both axes. To assess division plane specification, the colinearity of the nuclear and growth axes was uncoupled by treatment with pharmacological agents. Spatial correlations between the growth axis, telophase nuclei, and the division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…The appearance of an actin plate at the future cytokinetic plane is a distinctive feature in brown algae (Brawley and Robinson 1985;Bouget et al 1996;Karyophyllis et al 2000;Bisgrove et al 2003;Hable et al 2003;Bisgrove and Kropf 2004;Nagasato and Motomura 2009). In Silvetia and fucoid zygotes, the actin plate expanded centrifugally, and this expansion correlates with the outgrowth of the new cell partition membrane (Belanger and Quatrano 2000;Bisgrove and Kropf 2004).…”
Section: Actin Is Contributes In Transportation Of Cell Wall Materialmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of an actin plate at the future cytokinetic plane is a distinctive feature in brown algae (Brawley and Robinson 1985;Bouget et al 1996;Karyophyllis et al 2000;Bisgrove et al 2003;Hable et al 2003;Bisgrove and Kropf 2004;Nagasato and Motomura 2009). In Silvetia and fucoid zygotes, the actin plate expanded centrifugally, and this expansion correlates with the outgrowth of the new cell partition membrane (Belanger and Quatrano 2000;Bisgrove and Kropf 2004).…”
Section: Actin Is Contributes In Transportation Of Cell Wall Materialmentioning
confidence: 99%
“…The first cell division always arise perpendicular to the growth axis. Cytokinesis occurs where microtubules (MTs) from each centrosome intermingle (Nagasato and Motomura 2002a;Bisgrove et al 2003), and the centrosomes rotate so that cytokinesis occurs across the appropriate plane after mitosis. As a result of the asymmetrical division of the zygote, the thallus and rhizoid cells are formed.…”
Section: Introductionmentioning
confidence: 99%
“…First, the establishment of an internal cell asymmetry is required; and second, the positioning of the division plane and the spindle apparatus with respect to the axis is defined by the polarity of the cell. Accordingly, cytokinesis results in the asymmetric distribution of cellular components (Bisgrove et al, 2003) and presumably cell fate determinants. In mammalian cells, it has been shown that asymmetric mitosis is achieved by asymmetric labeling of peripheral centrosomal proteins for degradation when centrioles separate and migrate to opposite poles (Fuentealba et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, it has been shown that asymmetric mitosis is achieved by asymmetric labeling of peripheral centrosomal proteins for degradation when centrioles separate and migrate to opposite poles (Fuentealba et al, 2008). Moreover, in cases where the site of cytokinesis is not predetermined by a PPB, the cell division plane will bisect the spindle axis (Bisgrove et al, 2003). A PPB marks the position of the first mitotic division of the zygote (Webb and Gunning, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Polarity can be observed within 14-16 h AF when the rhizoid protuberance appears on the zygote surface. The rhizoid appearance is preceded by a series of processes, including asymmetric ion fluxes (Homblé and Léonetti 2007), redistribution of cytoskeletal elements (e.g., Bisgrove and Kropf 2001a, Bisgrove et al 2003) and targeted vesicular secretion (Kropf 1997). Subsequently, the zygote has a single axis of symmetry that defines the embryo growth axis, and normally the first division of the zygote is perpendicular to this axis and positioned by telophase nuclei (Bisgrove and Kropf 2004).…”
Section: Morphological Responsesmentioning
confidence: 99%